Enhancement of Study Skills for the Subject Career 3 (3D Drawing) for Mathayomsuksa 2 Students using the Canva Application - Taeja , Keetaphat; Ruengsri, Saowaluck (Community and Social Development Journal, 2023)
The objectives of this research were (1) to enhance study skills for the subject career 3 (3D Drawing) for Mathayomsuksa 2 students, (2) to develop teaching materials using the Canva application, and (3) to study the satisfaction of students in studying the subject career 3 (3D Drawing). The samples used in the research were grade 2/10 students, semester 1, academic year 2022, Sanpatong Wittayakhom School, Sanpatong District, Chiang Mai Province, total 36 people. Research tools included the Canva application, skill building guides, video clips of 3D drawing using the Canva application, and lesson plans. However, data analysis uses statistics of percentage, mean and standard deviation. The results of the study found that the enhancement of learning skills was at a high level = 4.43, the development of instructional materials using Canvas Image application was at a high level = 4.48, and overall student satisfaction was at a high level = 4.47. While educating students utilizing innovative teaching medium and analyzing student behavior in class, it was discovered that students paid attention and participated in class activities quite well.